1976
DOI: 10.1111/j.1467-1770.1976.tb00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Student Personality and Success in an English Language Program

Abstract: An original personality test based on Myers‐Briggs style statements is used to aid in screening and advisement of applicants to a freshman English tutorial program for foreign, minority, and Anglo‐American students. The test gives indications that it is strongly predictive of good and poor language‐study behavior as judged by language teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 3 publications
(1 reference statement)
0
11
0
Order By: Relevance
“…In the same vein, some researchers have attempted to isolate particular learner variables which might enhance or hinder progress in learning a foreign or second language (Chapelle & Roberts, 1986;Reid, 1987;Wenden & Rubin, 1987; O'Malley & Chamot, 1990; Oxford, 1990;Skehan, 1991). As cited in Dreyer and Vander Walt (1994), various research identified a number of variables that account for some of the differences in how students learn, including attitude and motivation (Gardner & Lambert, 1972;Gardner & Smythe, 1975;Gardner, Smythe, & Brunet, 1977), personality type/traits (Chastain, 1975;Guiora et al, 1975;Brodkey & Shore, 1976;Busch, 1982), learning styles (especially the field dependence/independence distinction) (Witkin et al, 1977a(Witkin et al, , 1977bBirckbichler & Omaggio, 1978;Hosenfeld, 1979;Hansen & Stansfield, 1981, 1982Chapelle & Roberts, 1986;Ried, 1987), and language learning strategies (Bialystok & Frö hlich, 1978;Bialystok, 1981;Wenden, 1983Wenden, , 1986aWenden, , 1986b; O'Malley, Chamot, Stewner-Manzanares, Kupper, & Russo, 1985a, 1985bWenden & Rubin, 1987;Oxford, 1989; O'Malley & Chamot, 1990; Oxford, 1990). By the same token, in recent years there has been an increasing awareness of the necessity in second or foreign language research and teaching to investigate cognitive aspects and gender differences that have undeniable effects on language learning and teaching.…”
Section: Introductionmentioning
confidence: 99%
“…In the same vein, some researchers have attempted to isolate particular learner variables which might enhance or hinder progress in learning a foreign or second language (Chapelle & Roberts, 1986;Reid, 1987;Wenden & Rubin, 1987; O'Malley & Chamot, 1990; Oxford, 1990;Skehan, 1991). As cited in Dreyer and Vander Walt (1994), various research identified a number of variables that account for some of the differences in how students learn, including attitude and motivation (Gardner & Lambert, 1972;Gardner & Smythe, 1975;Gardner, Smythe, & Brunet, 1977), personality type/traits (Chastain, 1975;Guiora et al, 1975;Brodkey & Shore, 1976;Busch, 1982), learning styles (especially the field dependence/independence distinction) (Witkin et al, 1977a(Witkin et al, , 1977bBirckbichler & Omaggio, 1978;Hosenfeld, 1979;Hansen & Stansfield, 1981, 1982Chapelle & Roberts, 1986;Ried, 1987), and language learning strategies (Bialystok & Frö hlich, 1978;Bialystok, 1981;Wenden, 1983Wenden, , 1986aWenden, , 1986b; O'Malley, Chamot, Stewner-Manzanares, Kupper, & Russo, 1985a, 1985bWenden & Rubin, 1987;Oxford, 1989; O'Malley & Chamot, 1990; Oxford, 1990). By the same token, in recent years there has been an increasing awareness of the necessity in second or foreign language research and teaching to investigate cognitive aspects and gender differences that have undeniable effects on language learning and teaching.…”
Section: Introductionmentioning
confidence: 99%
“…Personality traits have a significant contribution to learning . This fact is established in some previous studies correlating the performance of students in some specific subjects and professions , specifically in learning of language , medicine , engineering , nursing , software design , and online training . A five factor model has been proposed to correlate personality and academic performance and personality and job satisfaction .…”
Section: Introductionmentioning
confidence: 99%
“…Brodkey and Shore (1976) revealed that self-esteem appears to be an important variable in second language acquisition, particularly in view of cross-cultural factors of second language learning.…”
Section: Students' Variables Relevant For Creating Individualised Teamentioning
confidence: 99%